Unveiling Bihar's Atmospheric Crisis: A Synoptic Review of PM 2.5 Dynamics, Source Attribution, and Airshed Vulnerabilities in the Eastern Indo-Gangetic Plain (Bihar) - Krishna Roy; Amrita Raj Bharti; Umakant Kumar; Animesh Kumar; Shashi Prabha Dubey (International Journal of Pollution: Prevention & Control, 2026)
Bihar, situated in the pollution-trapping Indo-Gangetic Plain (IGP), faces a severe air pollution crisis characterized by annual PM2.5 concentrations of 80–100 μg m-3 exceeding WHO guidelines (5 μg m-3) and Indian NAAQS (40 μg m-3) by 4–6-fold. This review synthesizes data from CPCB/BSPCB monitoring, MODIS satellite retrievals, and peer-reviewed studies (2000–2025) to assess ambient air quality, sources, health impacts, policies, and research gaps in the state. PM2.5 and PM10 dominate, with rural levels rivaling urban centers like Patna (80–90% poor AQI days in winter/post-monsoon). Source apportionment reveals brick kilns (6,500+ units, 15–35% PM2.5), biomass burning (70% rural households), vehicular emissions, and transboundary inflows from UP/WB as key drivers. Winter inversions and declining rainfall exacerbate stagnation. Health burdens include respiratory/cardiovascular diseases, anemia (10–15% higher near kilns), and ~2% GSDP loss from premature mortality/productivity declines. Vulnerable groups-children, the elderly, and rickshaw pullers-face disproportionate risks. National Clean Air Program (NCAP) action plans promote zigzag kilns (82–85% adoption, 50–75% PM cuts), CNG/EVs, and CAAQMS expansion, yet implementation lags. Challenges persist: rural monitoring gaps, speciation deficits, and feedback on climate-pollution. This review calls for airshed-level management across IGP states, integrating dense sensors, emission inventories, and coupled climate-air models to achieve sustainable air quality improvements and co-benefits for health/economy.
Keywords: Air pollution; Bihar; PM2.5; brick kiln emissions; indo-gangetic plain